AN IDENTITY BETWEEN THE m-SPOTTY ROSENBLOOM-TSFASMAN WEIGHT ENUMERATORS OVER FINITE COMMUTATIVE FROBENIUS RINGS - Ozen, Mehmet; Shi, Minjia; Siap, Vedat (KOREAN MATHEMATICAL SOC, 2015)
This paper is devoted to presenting a MacWilliams type identity for m-spotty RT weight enumerators of byte error control codes over finite commutative Frobenius rings, which can be used to determine the error-detecting and error-correcting capabilities of a code. This provides the relation between the m-spotty RT weight enumerator of the code and that of the dual code. We conclude the paper by giving three illustrations of the results.
Keywords: byte error-control codes; m-spotty byte error; MacWilliams identity; weight enumerators; MACWILLIAMS TYPE IDENTITIES; CODES; Mathematics